Might we celebrate a small step? Beyond Deculpabilization in Amoris Laetitia - Fleming, Daniel J. (2019)
The article considers renewed interest in gradualism which has arisen from Pope Francis's recent exhortation Amoris Laetitia. It analyses the phenomenology of moral growth, and what subjective goodness is expressed by a person on that journey of growth. The article discusses Roger Burggraeve's recent work on 'deculpabilization' and the 'minus bonum' as categories which assist in understanding this subjective moral goodness. It argues that the minus bonum provides a way in which to understand the goodness of the moral subject who is unable to move beyond their stage of moral growth which is congruent with Amoris Laetitia, and which extends beyond existing understandings of gradualism.
Keywords: Amoris Laetitia; Pope Francis; Conscience; gradualism; Moral Development; Moral Growth